SARS-CoV-2 nucleic acid shedding is variable for every person - Daiana de Lima-Morales; Priscila Lamb Wink; Fabiana Caroline Zempulski Volpato; Joíza Lins Camargo; Fernanda de-Paris; Afonso Luís Barth (Revista da Sociedade Brasileira de Medicina Tropical, 2021)
Abstract INTRODUCTION: Considering the persistent positivity on RT-qPCR tests, the results of SARS-CoV-2 were monitored to evaluate the viral RNA shedding period. METHODS: Between March and June 2020, the sequential results of 29 healthcare workers’ were monitored using RT-qPCR. RESULTS: More than 50% of the individuals remained RT-qPCR positive after 14 days. Furthermore, this is the first study to describe positive RT-qPCR for SARS-CoV-2 in a healthcare worker with mild symptoms 95 days after the first positive test. CONCLUSIONS: Sequential RT-qPCR results were heterogeneous, and the viral RNA shedding period is unique for each person.